TH

cho a+b+c=0.cmr ab+2ac-abc+bc-\(a^2c-ac^2=-a^2-c^2\)

NN
28 tháng 7 2020 lúc 8:57

Xét tổng: \(ab+2ac-abc+bc-a^2c-ac^2+a^2+c^2\)ta có:

\(ab+2ac-abc+bc-a^2c-ac^2+a^2+c^2\)

\(=\left(a^2+2ac+c^2\right)+\left(ab+bc\right)-\left(abc+a^2c+ac^2\right)\)

\(=\left(a+c\right)^2+b\left(a+c\right)-ac\left(a+b+c\right)\)

\(=\left(a+c\right)\left(a+c+b\right)-ac\left(a+b+c\right)\)

mà \(a+b+c=0\)( giả thiết )

\(\Rightarrow ab+2ac-abc+bc-a^2c-ac^2+a^2+c^2=0\)

hay \(ab+2ac-abc+bc-a^2c-ac^2=-a^2-c^2\)( đpcm )

Bình luận (0)
 Khách vãng lai đã xóa